Aplikasi Teknologi Augmented Reality untuk Media Pembelajaran Olahraga Renang - Maria Lysis Sastra Kurnia Jastradaf; Yuli Asriningtias (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Swimming is a popular water sport, but the current learning process still relies on traditional printed books. To enhance the learning experience of this sport, this study aims to create and develop learning materials that use augmented reality technology. The research applies the waterfall software engineering method, which includes analysis, system design, implementation, and testing. During the analysis stage, observational data and questionnaires are collected to determine the application's scope. The system design stage includes conceptual design in the form of use cases and physical design in interface design. The design implementation phase is carried out using Unity 3D. The testing phase involves testing the feasibility of media and products using dichotomous scales and black box testing. Our research shows that augmented reality technology can be used as a tool for learning swimming sports. Our tests showed that the product feasibility is 94.7% and media feasibility is 95%. This proves that the application is highly feasible according to media experts and user respondents. The results of black box testing also show that the functionality of the system has been responsive, accurate, compatible, and successful to run all menus and features. Thus, this application can be distributed to be used as a medium for learning swimming sports.